Elevated levels of synaptic protein GAP‐43 associate with brain tauopathy, atrophy and cognition in Alzheimer's disease: Biomarkers (non‐neuroimaging) / Differential diagnosis. (7th December 2020) - Dhiman, Kunal; Villemagne, Victor LL; Eratne, Dhamidhu; Graham, Petra L; Fowler, Christopher J; Bourgeat, Pierrick; Li, Qiao‐Xin; Collins, Steven; Bush, Ashley I; Rowe, Christopher C; Ames, David; Masters, Colin L; et al.
Abstract: Background: Synaptic dysfunction is an early pathophysiological event, which associates with cognitive aberrations in Alzheimer's disease (AD). Growth associated protein 43 (GAP‐43) is a nervous tissue specific protein, which plays a crucial role in axon formation, growth and synaptic plasticity. The current study evaluated the utility of cerebrospinal fluid (CSF) GAP‐43 in diagnosing AD, and its association with neuropathological and cognitive changes in AD, using CSF samples of participants from the Australian Imaging, Biomarkers and Lifestyle study of ageing (AIBL). Method: The study participants (n=218) were clinically classified into healthy controls (HC, n=156), mild cognitive impairment (MCI, n=34) and AD (n=28). CSF levels of core CSF biomarkers (amyloid beta‐42, Ab42; total‐tau, T‐tau; phosphorylated‐tau, P‐tau) were assessed using commercial enzyme linked immunosorbent assays (ELISA). CSF GAP‐43 levels were assessed using a sandwich ELISA, based on the monoclonal antibody NM4 (Fujirebio, Ghent, Belgium) and a polyclonal GAP‐43 antibody (ABB‐135, Nordic Biosite, Täby, Sweden). Association of GAP‐43 with core CSF biomarkers was assessed via a linear correlation analysis. Multiple regression analyses were undertaken to assess the utility of GAP‐43 for predicting baseline amyloid load (measured by standardized uptake value ratio, SUVR), brain atrophy (measured by hippocampal volume) and cognition (measured by Mini‐Mental State Examination, MMSE and Clinical Dementia Rating Sum of Boxes, CDR‐SB). Result: GAP‐43 levels were significantly elevated in AD compared to HC (p=0.001) and MCI (p= 0.036) and distinguished AD from HC with an area under the receiver operating characteristic curve (AUC) of 0.72. CSF GAP‐43 levels were significantly correlated with CSF T‐tau (r=0.84, p<0.001) and P‐tau (r=0.87, p<0.001), but not with CSF Ab42 (r=0.05, p=0.470). CSF levels of GAP‐43 significantly predicted baseline hippocampal volume ( b =−0.05, standardized b =−0.16, p =0.027), and cognition as measured by MMSE ( b =−0.28, standardized b =−0.14, p =0.039) and CDR‐SB ( b =0.28, standardized b =0.22, p =0.001), after controlling for covariates. CSF GAP‐43 levels also significantly predicted baseline amyloid ( b =0.05, standardized b =0.24, p <0.001). Conclusion: As an AD biomarker, CSF GAP‐43 could be used to track the stage‐ and state‐associated synaptic aberrations that occur in the AD brain, and to understand the impact of stage‐associated synaptic aberrations on cognition and brain atrophy.